Diseño de una propuesta de difusión y comunicación de los procedimientos a través del portal de compras públicas - Vallejo Guangaje, Karina (2012)
This paper aims to disseminate and communicate procedures dynamic procurement of goods, services and works through the portal public procurement resulting in improved image and Integrated communication state institutions with the aim of eliminate corruption in government agencies. The development of this research will be structured into five chapters: first chapter deals with the field of Public Procurement in Ecuador, background, strategies against corruption, fairness, honesty and truthfulness in the civil service; The second chapter lists the objectives of the System National Public Procurement, the main actors, accountability the public servant and the creation of the National Institute of Public-Procurement INCOP; The third chapter describes step by step procedures public procurement aims to achieve the user charge the acquisition of goods, services and works, not standardized standardized tools used efficiently shopping portal public; then in chapter four possible causes it is detected causing that state institutions do not apply the procedures dynamic for acquisitions according to the Organic Law of the National System Public Procurement and the regulations in force; and finally analyzes main findings and results of this work.